Evaluation Method of Distribution Network Carrying Capacity Based on Bayesian Network. Issue 1 (1st December 2022) - Wang, Ke; Yang, Sumin; Zhang, Xu; Cui, Jimin; Zhang, Dongsheng; Wei, Yuren
Abstract: The high-permeability distributed new energy is connected to the distribution network, which aggravates the fluctuation and uncertainty of the distribution network. In order to gradually improve the scientificity and accuracy of the distributed new energy-carrying capacity evaluation, it has become an essential means to solve the problem of wind and light abandonment by means of high-voltage DC channels to realize the power transmission from the new energy-rich areas and promote the interconnection and carrying of multiple areas. This paper proposes a calculation model of the maximum carrying capacity of multi-distributed power sources accessing the power network. The Bayesian network model limits the voltage offset, voltage fluctuation, short circuit current, and subsequent current related to electrical protection. Based on the dynamic sensitivity of the constraint index to distributed power capacity, a segment solution method is proposed to deal with various constraints. Through experimental analysis, it is proved that the speed of promoting the model in this paper is faster. It has an optimization effect for more constraints. This paper can reasonably evaluate the carrying capacity of the existing distribution network for distributed new energy, and provide support for further research on the carrying capacity improvement strategy of high-permeability and fluctuating new energy.